Synthesis, characterization and application of 1-(2-cyanoethyl)-3-(3-methoxypropane)imidazolium bromide for CO2 capture - Ravichandar, S. (EDP Sciences, 2017)
Amine scrubbing is dominating in carbon dioxide (CO2) capturing technology because of its high affinity towards CO2. However, the drawbacks of amine solvents are its high corrosivity and volatility. Ionic liquids (ILs) have gained a lot of attention in recent years for CO2 capturing and have been proposed to be one of the promising alternative to the conventional solvents. The objective of this research is to design a new imidazolium based ether-nitrile functionalized ionic liquid of low viscosity to improve CO2 capturing. The molecular structure of the ionic liquid were confirmed by 1H NMR, 13C NMR and FTIR. The thermal properties; glass transition temperature, thermal decomposition temperature, and their physical properties; water content and density were determined. The solubility of CO2 in the synthesized ionic liquid was measured using pressure drop method. They showed high thermal stability above 200°C and the glass transition temperature was-49.80°C. The CO2 sorption in the newly synthesized IL was 0.08, 0.12, 0.29, 1.01, 2.30 mol of CO2/mol of IL at pressures 1, 5, 10, 15 and 20 bar respectively. © The Authors, published by EDP Sciences, 2017.